Comparative transcriptomic evidence of physiological changes and potential relationships in vertebrates under different dormancy states - Niu, Yu-Han; Guan, Li-Hong; Wang, Cheng; Jiang, Hai-Feng; Li, Guo-Gang; Yang, Lian-Dong; He, Shun-Ping (Dōngwùxué yánjiū, 2024)
Dormancy represents a fascinating adaptive strategy for organisms to survive in unforgiving environments. After a period of dormancy, organisms often exhibit exceptional resilience. This period is typically divided into hibernation and aestivation based on seasonal patterns. However, the mechanisms by which organisms adapt to their environments during dormancy, as well as the potential relationships between different states of dormancy, deserve further exploration. Here, we selected and as the primary subjects to study hibernation and aestivation, respectively. Based on histological and transcriptomic analysis of multiple organs, we discovered that dormancy involved a coordinated functional response across organs. Enrichment analyses revealed noteworthy disparities between the two dormant species in their responses to extreme temperatures. Notably, similarities in gene expression patterns pertaining to energy metabolism, neural activity, and biosynthesis were noted during hibernation, suggesting a potential correlation between hibernation and aestivation. To further explore the relationship between these two phenomena, we analyzed other dormancy-capable species using data from publicly available databases. This comparative analysis revealed that most orthologous genes involved in metabolism, cell proliferation, and neural function exhibited consistent expression patterns during dormancy, indicating that the observed similarity between hibernation and aestivation may be attributable to convergent evolution. In conclusion, this study enhances our comprehension of the dormancy phenomenon and offers new insights into the molecular mechanisms underpinning vertebrate dormancy.